Atividade anti-Leishmania do óleo essencial de Tetradenia riparia associado ao cetoconazol ou a anfotericina B, in vitro - Terron, Mariana de Souza (2017)
The objective of this work was to evaluate the interaction of the essential oil of Tetradenia riparia (TrEO) and ketoconazole (KET) or amphotericin B (AmB) in Leishmania (Leishmania) amazonensis promastigotes, and murine peritoneal cells to propose an alternative therapy for leishmaniasis. For this, the parasites and the murine peritoneal cells were exposed to different concentrations of TrEO, KET and AmB individually and combined using the micro-dilution checkerboard technique and the XTT colorimetric method. We analyzed the data according to the Chou-Talallay combination index method, using CompuSyn software, calculating lethal dose for 50% of parasites (LD50) and cytotoxicity for 50% of murine peritoneal cells (CC50) for individual and combined tests, besides to the interaction parameters as combination index (CI), dose-reduction index (DRI). The results obtained yielded two manuscripts: "Anti-Leishmania activity of the essential oil association of Tetradenia riparia and ketoconazole" and "Interactions between the essential oil of Tetradenia riparia and amphotericin B in Leishmania (Leishmania) amazonensis promastigotes". The LD50 for TrEO, KET and AmB tested individually after 24 hours of incubation was 0.34; 0.70 and 0.54 μg / mL respectively, and the CC50 was 0.125; 40 and 10.36 μg / mL, respectively. In the interaction between TrEO and KET, were evaluated as combinations of 1:120; 1:60 and 1:30 (μg / mL TrEO / μg / mL KET). The combination of 1:60 showed to be synergistic, reducing the LD50 of TrEO and KET in 50% and 88% respectively, besides allowing the viability of more than 58% of the murine peritoneal cells; the combinations of 1:20 and 1:30 were additive, but cell viabilities were less than 50%. In the interactions between TrEO and AmB, we evaluated the ratios of 1:1.2; 1:0.6 and 1:0.3. We found an effect moderately synergistic in the interaction ratio of 1:0.6 and 1:0.3, reducing the dose of AmB and TrEO by up to 87% and 60%, respectively, although in the combination of 1:1.2 their effects were antagonistic. These results suggest that the combination of Tetradenia riparia essential oil and ketoconazole or amphotericin B may be an alternative treatment for American tegumentary leishmaniasis, but amastigote and in vivo studies should be conducted to confirm this possibility.